Issue of Compliance Control Efficiency at Nuclear Industry Enterprises in Economic Crisis Conditions - M. V. Golovko; A. N. Setrakov; A. V. Antsibor; S. P. Agapova; I. A. Ukhalina; N. A. Efimenko (Глобальная ядерная безопасность, 2022)
This article discusses the benefits of implementing compliance control in enterprises. Analytical materials of authoritative organizations in the field of compliance are used to substantiate the author's position. Experience is considered Rosatom State Corporation development and implementation of compliance discipline. Indicators are given that testify to the effectiveness of the compliance control system at the enterprise. The necessity and efficiency of using digitalization tools for compliance control is substantiated.